«
  
»
(2x²-5)²=39+10.(2x²-5)


RESOLVENDO

( 2x²-5)²=39+10.(2x²-5)
4x²-25=49.4x²-25
4x²-4x²=49-25+25
x²=49

Observe que, \( (2x^2-5)^2=4x^4-20x^2+25 \).
Assim, a equação dada é equivalente a:
\( 4x^4-20x^2+25=39+10\cdot(2x^2-5) \)
\( 4x^4-20x^2+25=39+20x^2-50 \)
Assim, \( 4x^4-40x^2+36=0 \), ou seja, \( x^4-10x^2+9=0 \)
Vamos chamar \( y=x^2 \).
Deste modo, como  \( (x^2)^2-10x^2+9=0 \), então, \( y^2-10y+9=0 \).
Temos que, \( \Delta=(-10)^2-4\cdot1\cdot9=100-36=64 \).
Logo, \( y=\dfrac{10\pm\sqrt{64}}{2}=\dfrac{10\pm8}{2} \), isto é, \( y’=9 \) e \( y’’=1 \).
Portanto, \( x^2=9 \) ou \( x^2=1 \).
Com isso, obtemos \( x=\pm\sqrt{9}=\pm3 \) e \( x=\pm\sqrt{1}=\pm1 \).
Logo, \( S=\{-1,3, 1, 3\} \).



TAREFAS SIMILARES: